Experiencing Disharmony: Representing the Imbalance in the Human–Nature Relationship Through Drawing - Khayla Indiva Pratanto; Dikdik Sayahdikumullah; Dadang Sudrajat (ATRAT: Jurnal Seni Rupa, 2025)
This article discusses the Drawing series “Experiencing Disharmony” as a reflection on the imbalance between humans and nature due to anthropocentric dominance. Based on mountain trekking experiences, the work depicts human alienation within vast and unpredictable landscapes, emphasizing submission to natural laws. The theoretical approach draws from mimesis, Romantic aesthetics, Apollonian–Dionysian duality, Gregory Bateson’s anti-anthropocentrism, and Raffaele Milani’s concept of landscape as a contemplative space. A research-based art practice is used, with landscape photography as the visual foundation. Layered pastel and charcoal lines on large paper record both physical and inner experiences. A small human figure facing away from the viewer reinforces alienation. Visual disharmony is conveyed through disproportional scale, metaphorical composition, and color limitations as an ecological awareness. Each of the six drawings is subtitled with geographic coordinates to highlight landscape as a reflective site.